On Jan Twardowski’s indexical biblionyms - Yermolenko, S.S. (Мовознавство, 2014)
The author focuses on the titles of poetic works of the Polish poet Jan Twardowski which he calls
indexical, explaining their specific nature as determined by semiotic features of motivation proper
to them as poetic text names, on the one hand, and by their role as an integral part of the poetic text,
on the other. Статтю присвячено тим назвам віршів польського поета Яна Твардовського, що їх автор
окреслює як індексальні, пов’язуючи специфіку цих бібліонімів з умотивованістю, властивою
їм як позначенням поетичного тексту, з одного боку, і з їхньою роллю інтегральних
складників поетичного тексту, — з другого.